(untitled) (Élisée - Revista de Geografia da UEG, 2020)
Multitemporal analysis of the river system of the Araguaia river, Aruanã – Goiás, Brazil Abstract: This study aimed to perform a multitemporal analysis of the morphological evolution of the river system in the middle stretch of the Araguaia River, upstream of the confluence with the Rio Vermelho, in Aruanã - Goiás, and to analyze the main changes in erosion and sedimentation processes, lateral migration and sedimentation in the fluvial system, in the years 1984, 2000, 2016 and 2018. The data of the morphological elements, erosive and sedimentary processes of the channel were obtained through the segmentation of images and unsupervised classification (pixel to pixel),using images from Landsat 5 and Landsat 8 satellites, with spatial resolution of 30 meters, as well as visual inspection, validation of data and correction of polygons. Photographic and aerial images were collected with UAVs, which were used as support in the visual interpretation of the morphological elements realized in the mapping. The interpretations indicate a increase in sediment areas, with a 89.8% increase in sedimentary deposits between 1984 (2.16 km²) and 2018 (4.10 km²), in addition to the morphological changes in confluence and bar typologies thus confirming the strong tendency of sediment accumulation in this part of the river system, which are characterized as a response to the land use and occupation processes in the Araguaia river basin in recent years.